Health, well-being and social relations in a changing neighbourhood. (30th September 2020) - Lund, R; Christensen, U; Mathisen, J; Srivarathan, A; Molbo, D; Kristiansen, M
Abstract: The main purpose of the study is to examine the development in health, wellbeing and social relations among middle-aged and older residents during a four-year period from 2018-2021 in a Danish multi-ethnic social housing area undergoing large structural changes in the built environment. In addition, to develop two interventions with a focus on ensuring social cohesion in the area during the study period. This presentation will provide an overview of the study outline. The presentation will include a description of the study area, the political decisions that have led to the structural changes, the study population and a short overview of the aims and planned sub-studies. To prepare for the workshop discussion of the challenges, advantages and possibilities with the multi-methods approach this is followed by a short introduction to the different methods applied (a three-wave survey and qualitative data as well as two co-created interventions). The study is furthermore including a 'natural experiment' (N∼6.000) with a neighbouring non-profit social housing area not undergoing structural changes as the control area based on register data. The user-engagement in the design of study will be shortly described for example by their involvement in intervention development and by the involvement of citizen representatives and representatives from the Municipality and local non-governmental organizations in the design and execution of the study. Finally, the inclusion of graphical facilitation as a communication tool will be introduced.